BRITANNICA ALL NEW CHILDREN'S ENCYCLOPEDIA : WHAT WE KNOW & WHAT WE DON'T - Lloyd, Christopher, 1968- (Tonbridge, Kent : Britannica Books, 2020)
This substantial, gifty, and compellingly browsable children's encyclopedia takes Britannica's reputation for authentic, trustworthy information and brings it to a whole new audience. The gorgeous volume explores a wide range of kid-friendly topics, using text, illustrations, infographics, and photography, all in an upscale package that blings with the best of them. In keeping with Britannica's reputation for expert involvement, each spread include a credit to the expert involved with its creation, and special features highlight some of the most intriguing unsolved puzzles in science, archaeology, history, and engineering. Chapter topics include Universe, Earth, Material World, Living World, Being Human, Ancient Civilizations, Medieval to Modern, and Today's World and Beyond.
Includes bibliographical references and index.
Keywords: Children's encyclopedias and dictionaries; Encyclopedias